The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.wear.2019.01.121
|View full text |Cite
|
Sign up to set email alerts
|

Influence of relative humidity and low temperature hydrothermal degradation on fretting wear of Y-TZP dental ceramics

Abstract: Dental pieces are subjected to constant friction due to grinding during mastication and mouth disorders such as bruxism. Therefore, wear resistance of Y-TZP materials used for dental prostheses must be investigated. In this work, the influence of humidity and low temperature hydrothermal degradation (LTD) in 3Y-TZP ceramics subjected to fretting has been evaluated. A 100% r.h. reduces the effects of wear due to the lubricative effect of water, compared to those at ambient r.h. COF, wear volume and damage are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, an important characteristic of these materials is completely stabilized zirconia tetragonal (t) phase with the addition of an oxide (Y 2 O 3 , CeO 2 ,…), for example, with ~3.0 mol% of yttria for dental applications. This is important because when Y-TZP materials are subjected to humidity at 25-280°C [14][15][16], a sharp decline in their mechanical properties occurs over time. This phenomenon is referred to as low-temperature degradation (LTD) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…However, an important characteristic of these materials is completely stabilized zirconia tetragonal (t) phase with the addition of an oxide (Y 2 O 3 , CeO 2 ,…), for example, with ~3.0 mol% of yttria for dental applications. This is important because when Y-TZP materials are subjected to humidity at 25-280°C [14][15][16], a sharp decline in their mechanical properties occurs over time. This phenomenon is referred to as low-temperature degradation (LTD) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al [ 22 ] showed that the partial slip region was always associated with slight wear, the mixed region formed cracks, and the gross slip region mainly produced wear and damage of materials. A lot of studies showed that there were many influencing factors on the fretting wear behavior of materials, including frequency [ 23 , 24 ], normal force [ 25 , 26 ], displacement amplitude [ 27 , 28 ], and even temperature [ 29 , 30 ], surface roughness and so on [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite zirconia's good mechanical, chemical and esthetic properties, more information is required regarding the effects that LTD might produce, a phenomenon known to cause spontaneous "ageing" and loss of mechanical properties in this material [17]. This phenomenon occurs when zirconia is exposed to environments of humidity and temperatures between 20-300°C; these conditions lead to a spontaneous transformation from tetragonal (t) phase to monoclinic (m) phase in the material structure [18].…”
Section: Introductionmentioning
confidence: 99%